PENINGKATAN PENGETAHUAN WANITA USIA SUBUR TENTANG DETEKSI DINI KANKER PAYUDARA SECARA RUTIN MELALUI PELATIHAN METODE SADARI DI DESA RUGEMUK - Umi Salmah; Izzah Dienillah Saragih; Risanti Febrine Ropita Situmorang; Fitri Khairani; Arifa Masyitah Panjaitan; Ismil Khairi Lubis (Yayasan Education and Social Center, 2023)
The rate of breast cancer in Indonesia reaches 42.1 people per 100,000 population, with an average death from this cancer reaching 17 people per 100,000 population. The prevalence of breast cancer in North Sumatra is 4% and is included in Indonesia's top 10 highest categories of 33 provinces.Pantai Labu Village is a coastal area with Dominant WUS characteristics. Therefore, it is necessary to carry out community service activities in the form of Breast Self-Examination (BSE) activities to detect early breast cancer. The results of the discussion found that there were changes in knowledge, attitudes, and actions in the community regarding BSE activities. It is hoped that the community can apply knowledge about BSE as a routine early detection of breast cancer, and the local Puskesmas is expected to be able to follow up on BSE periodically